RIFM fragrance ingredient safety assessment, 3, 5-dimethylcyclohex-3-ene-1-methyl acetate, CAS Registry Number 67634-25-7. (15th December 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Highlights: 3, 5-Dimethylcyclohex-3-ene-1-methyl acetate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.